Criminal psychology - Canter, David (Topics in applied psychology, 2017)
About the author -- Foreword to second edition -- Psychology and the criminal process -- The basis of criminality -- Biological explanations of crime -- Psychological explanations of crime -- Social explanations of crime -- Varieties of crime -- Acquisitive crime -- Domestic violence -- Sexual offences -- Homicide and serial killing -- Gangs, organised crime and terrorism -- Interacting with criminals -- Testimony and interviewing -- Deception and fraud -- Psychology and investigations -- Areas of application -- Psychology and the police -- Psychology in court -- Psychology in prison -- Concerning victims -- The future of psychology and crime -- Notes on publications and accessing them -- References -- Index